The influence of celebrity endorsers, product variations and product quality on scarlett whitening consumers' buying interest - Rani Jeniarta Sigalingging; Ella Silvana Ginting; Purnaya Sari Tarigan (Indonesia Accounting Research Journal, 2022)
This study aims to determine the Influence of Celebrity Endorsers, Product Variations and Product Quality on Scarlett Whitening Consumers' Buying Interest (Case Study of Scarlett Whitening Official Instagram Followers). The type of research used in this study is quantitative research. The sample determination technique in the study used a nonprobability sampling technique with the quota sampling method. It was done by distributing the questionnaire online using a google form against 100 samples, namely on Scarlett Whitening's Instagram followers. The data analysis method used is multiple linear regression analysis. The results of the partial test (Test t) showed that the celebrity endorser variables and product variations did not have a significant effect on Scarlett Whitening Consumer Buying Interest while the Product Quality variable had a significant effect on Scarlett Whitening Consumer Buying Interest. Furthermore, the results of simultaneous testing (Test F) showed that the three independent variables (Celebrity Endorser, Product Variation, and Product Quality) influenced the dependent variable (Consumer Buying Interest). The coefficient of determination (Adjusted R Square) shows that the variables Celebrity Endorser, Product Variation and Product Quality can explain the variation in Consumer Buying Interest is 63.8% while the remaining 36.2% is explained by other variables that were not studied in this study.